Bio-Use Power of Insecticide Metarizhium anisopliae in Controlling Oryctes rhinoceros in Palm Oil - Idum Satia Santi; Nur Fajar Ahmad; Olivia Elfatma; Nur Azizah Uswatun Hasanah (Tropical Plantation Journal, 2022)
Horn beetles (Oryctes rhinoceros) are among the pests in oil palm plantations. This study aims to find out the usefulness of Metarhizium anisopliae with a combination of various ways of application and dosage to suppress the development of Oryctes rhinoceros larvae in unproditioned plants (TM) in oil palm plantations. The experiment was conducted using a complete randomized design of two factors, namely eight treatments and three repeats, namely, the application of mushrooms M. anisopliae formulation of rice flour with a dose of 15 g / m2, 20 g / m2, 30 g / m2 and application of mushroom M. anisopliae dissolved in 1L water at doses of 15 g, 20 g, 25 g and 30 g. Observational data that the number of larvae infected and larval mortality were further analyzed by One Way Anova and further tested duncan with a real level of 5%. The observations showed differences in the number of infected larvae and the mortality of the larvae. The highest number of infected larvae and larval mortality occur in the treatment of M. anisopliae fungal application.